PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PERHATIAN DAN PRESTASI BELAJAR SISWA (Studi pada Mata Pelajaran Matematika Siswa Kelas II SD Kecamatan Pagar Alam Utara) - Mersianah Mersianah; Johanes Sapri (DIADIK, 2021)
This study aims to describe the application of demonstration method to increase student attention and learning achievement. This research uses the Classroom Action Research (CAR) method which is carried out in three cycles with four stages consisting of planning, implementation, observation, and reflection. This research also uses quasi experiment. The subject of the study was the second semester of II grade students in the 2020/2021 school year at SD Negeri 2Pagar Aam, totaling 25 students. Whereas the quasi-experiments were IIA and IIB grade students in SD Negeri 7 Pagar Alam, each of which numbered 25 students. Data collection instruments in this study used observation sheets and tests. Analysis of research data using statistical averages (mean), percentages and t-test. The results showed that the application of the demonstration method in learning activities could increase the attention and learning achievement of grade II students of SD Negeri 2 Pagar Alam